A Series of New Hydrazone Derivatives: Synthesis, Molecular Docking and Anticholinesterase Activity Studies - Bozbey, Irem; Ozdemir, Zeynep; Uslu, Harun; Ozcelik, Azime Berna; Senol, Fatma Sezer; Orhan, Ilkay Erdogan; Uysal, Mchtap (Bentham Science Publ Ltd, 2020)
Background: Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) are known to be serine hydrolase enzymes responsible for the hydrolysis of acetylcholine (ACh), which is a significant neurotransmitter for regulation of cognition in animals. Inhibition of cholinesterases is an effective method to curb Alzheimer's disease, a progressive and fatal neurological disorder. Objective: In this study, 30 new hydrazone derivatives were synthesized. Then we evaluated their anticholinesterase activity of compounds. We also tried to get insights into binding interactions of the synthesized compounds in the active site of both enzymes by using molecular docking approach. Methods: The compounds were synthesized by the reaction of various substituted/nonsubstituted benzaldehydes with 6-(substitute/nonsubstituephenyl)-3(2H)-pyridazinone-2-yl propiyohydrazide. Anticholinesterase activity of the compounds was determined using Ellman's method. Molecular docking studies were done by using the ADT package version 1.5.6rc3 and showed by Maestro. RMSD values were obtained using Lamarckian Genetic Algorithm and scoring function of AutoDock 4.2 release 4.2.5.1 software. Results: The activities of the compounds were compared with galantamine as cholinesterase enzyme inhibitor, where some of the compounds showed higher BChE inhibitory activity than galantamine. Compound F1(11) was shown to be the best BChE inhibitor effective in 50 mu M dose, providing 89.43% inhibition of BChE (IC50=4.27 +/- 0.36 mu M). Conclusion: This study supports that novel hydrazone derivates may be used for the development of new BChE inhibitory agents.
Keywords: Alzheimer's disease; AChE inhibitor; BChE inhibitor; 3(2H)-Pyridazinone; hydrazone; molecular docking